Response of Soybean (Glycine Max (L.) Merrill) to Organic and Inorganic Fertilizers - Simbulan, Jonie C; de Jesus, Norman (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
The effects of organic and inorganic fertilizers on the growth and yield performance of soybean was evaluated at ALIAS R & DE Center, Pampanga State Agricultural University, PAC, Magalang, Pampanga from December 2017 to March 2018. It was laid out in the field according to the procedures of randomized complete block design (RCBD) with three replications. The treatments tested were T1 – No fertilizer application, T2 – 500 kg/ha of Power Organic, T3 – 21.74 kg/ha of Urea and 150 kg/ha of Super Phosphate, T4 – 250 kg/ha of Power Organic + 10.87 kg/ha of Urea and 75 kg/ha of Super Phosphate, T5 – 375 kg/ha of Power Organic + 5.44 kg/ha of Urea and 37.5/ha of Super Phosphate, T6 – 125 kg/ha of Power Organic + 16.31 kg/ha of Urea and 112 kg/ha of Super Phosphate. Results revealed that all organic and inorganic fertilizers applied crops were significantly different in terms of days to flowering, plant height at flowering, length of pods, weight of 100 seeds and computed seed yield per hectare. Cost and return analysis reveals that the highest net income and return of investment was derived from the combination of 50 % organic and 50 % inorganic fertilizer. Conjunctive use of organic and inorganic fertilizer, that is, 50 % recommended rate of organic fertilizer (Power organic) along with 50 % recommended rate of inorganic fertilizer (Urea and Super Phosphate) can enhance the growth and yield performance of soybean and can help the farmer to increase their production with higher net income.